The planned sub-centres for riyadh city, a shift towards polycentric metropolitan development - Al-Mayouf, Abdualelah (2008)

(untitled)
Riyadh city, the capital of Saudi Arabia, will be transformed in the near future to a polycentric model which corresponds to the characteristic of modern cities. The city is now a monocentric, and its urban form was affected by the expansion of low-density residential areas. Riyadh has a population of just over four million inhabiting a developed land of nearly 1200 km2. The city was and will continue to be a focal point of attraction for migration, economic activities, and many key urban services. In February 2007, new regulations for the city new sub-centres were approved by the High Commission for the Development of Riyadh. This planned change for the city which is part of a polycentric metropolitan strategy tends to create new developments of sub-centres that could accommodate some key urban services outside the central business district as well as offering employment opportunities. This paper explores the reasons behind such changes, and the new regulations proposed for the planned sub-centres.